Transcatheter aortic valve-in-valve implantation to treat aortic para-valvular regurgitation after TAVI. (1st October 2022) - Landes, Uri; Morelli, Olga; Danenberg, Haim; Sathananthan, Janarthanan; Backer, Ole De; Sondergaard, Lars; Abdel-Wahab, Mohamed; Yoon, Sung-Han; Makkar, Raj R.; Thiele, Holger; Kim, Won-Keun; Hamm, Christian; et al.
Abstract: Background: Para-valvular regurgitation (PVR) after transcatheter aortic valve (TAV) implantation is associated with increased mortality. Redo-TAVI may be applied to treat PVR, yet with unknown efficacy. We thought to assess redo-TAVI efficacy in reducing PVR using the Redo-TAVI registry (45 centers; 600 TAV-in-TAV cases). Methods: Patients were excluded if redo-TAVI was done urgently ( N  = 253), for isolated TAV stenosis ( N  = 107) or if regurgitation location at presentation remained undetermined ( N  = 123). The study group of patients with PVR ( N  = 70) were compared against patients with intra-valvular regurgitation (IVR) ( N  = 41). Echocardiographic examinations of 67 (60%) patients were reassessed in a core-lab for data accuracy validation. Results: Core-lab examination validated the jet location in 66 (98.5%) patients. At 30 days, the rate of residual AR ≥ moderate was 7 (10%) in the PVR cohort vs. 1 (2.4%) in the IVR cohort, p  = 0.137. The rate of procedural success was 53 (75.7%) vs. 33 (80.5%), p  = 0.561; procedural safety 51 (72.8%) vs. 31 (75.6%), p  = 0.727; and mortality 2 (2.9%) vs. 1 (2.4%), p  = 0.896 at 30 days and 7 (18.6%) vs. 2 (11.5%), p  = 0.671 at 1 year, respectively. Of patients with residual PVR ≥ moderate at 30 days, 5/7 occurred after implanting balloon-expandable in self-expanding TAV and 2/7 after balloon-expandable in balloon-expandable TAV. Conclusions: This study puts in perspective redo-TAVI efficacy and limitations to treat PVR after TAVI. Patient selection for this and other therapies for PVR needs further investigation. Highlights: Para-valvular regurgitation (PVR) after TAVI is associated with increased mortality. Redo-TAVI reduced PVR in 90% of patients with PVR after TAVI. AR persisted in 10% of patients with PVR vs. 2.4% with intra-valvular AR, p = 0.137. Procedural success, safety and mortality were comparable.